Feasibility and Rationale for Incorporating Frailty and Cognitive Screening Protocols in a Preoperative Anesthesia Clinic. (September 2019) - Amini, Shawna; Crowley, Samuel; Hizel, Loren; Arias, Franchesca; Libon, David J.; Tighe, Patrick; Giordano, Chris; Garvan, Cynthia W.; Enneking, F. Kayser; Price, Catherine C.
Abstract : BACKGROUND: Advanced age, frailty, low education level, and impaired cognition are generally reported to be associated with postoperative cognitive complications. To translate research findings into hospital-wide preoperative assessment clinical practice, we examined the feasibility of implementing a preoperative frailty and cognitive assessment for all older adults electing surgical procedures in a tertiary medical center. We examined associations among age, education, frailty, and comorbidity with the clock and 3-word memory scores, estimated the prevalence of mild to major cognitive impairment in the presurgical sample, and examined factors related to hospital length of stay. METHODS: Medical staff screened adults ≥65 years of age for frailty, general cognition (via the clock-drawing test command and copy, 3-word memory test), and obtained years of education. Feasibility was studied in 2 phases: (1) a pilot phase involving 4 advanced nurse practitioners and (2) a 2-month implementation phase involving all preoperative staff. We tracked sources of missing data, investigated associations of study variables with measures of cognition, and used 2 approaches to estimate the likelihood of dementia in our sample (ie, using extant data and logistic regression modeling and using Mini-Cog cut scores). We explored which protocol variables related to hospital length of stay. RESULTS: The final implementation phase sample included 678 patients. Clock and 3-word memory scores were significantly associated with age, frailty, and education. Education, clock scores, and 3-word scores were not significantly different by surgery type. Likelihood of preoperative cognitive impairment was approximately 20%, with no difference by surgery type. Length of stay was significantly associated with preoperative comorbidity and performance on the clock copy condition. CONCLUSIONS: Frailty and cognitive screening protocols are feasible and provide information for perioperative care planning. Challenges to clinical adaptation include staff training, missing data, and additional administration time. These challenges appear minimal relative to the benefits of identifying frailty and cognitive impairment in a group at risk for negative postoperative cognitive outcome.